FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA KEPUTUSAN PETANI SP4 MENGGUNAKAN PEMBIAYAAN PADA PERBANKAN DI KABUPATEN MIMIKA - Triswantika Br Simamora; Benedikta Uba Deran; Rahmat Arapi (Adisam Publisher, 2025)
This study aims to determine the factors influencing farmers' decisions in using financing from banks. The method used in this study is the associative method. The data collection technique in this study is direct data collection, namely by means of survey results, interviews and distributing questionnaires to farmers in SP4 in Mimika Regency. The analysis tool in this study uses Multiple Linear Regression analysis. Based on the results of the analysis, it shows that the guarantee factor does not have a significant effect on farmers' interest while the administration factor has a significant effect on farmers' interest in not using financing from banks in Mimika Regency